Model for resolving election violations through Indonesian Election Body and Constitutional Court - Borman, M. Syahrul; Marwiyah, Siti; Cornelis, Vieta Imelda; Lazuardi, Irwan; Kaewhanam, Phimlikid (Faculty of Law, University of Muhammadiyah Malang, 2024)
This study formulates a model for resolving disputes over election violations through the Election Supervisory Body and the Constitutional Court in Indonesia. This research analyses juridical and normative theories, policies, and legal decisions, as well as studies of cases of election violations in 2014 and 2019. This research method uses qualitative research with a grounded theory approach and a normative juridical approach. The data sources comprise primary and secondary legal materials. The results of this study show that 1) Problems with violations of the electoral process and disputes over election results have not been resolved properly. 2) The model of resolving violations of the electoral process and disputes over election results is with a settlement model approach through the Application of the Critical Attitude Model of Public Militancy and Law Enforcement Militancy by the Election Supervisory Body and the Constitutional Court.